Stressful Life Events and Binge Eating Disorder. (18th July 2014) - Degortes, Daniela; Santonastaso, Paolo; Zanetti, Tatiana; Tenconi, Elena; Veronese, Angela; Favaro, Angela
Abstract Although there is evidence about the role played by stressful life events (SE) in the pathogenesis of eating disorders, few studies to date have explored this problem in binge eating disorder (BED). The aim of the present study was to examine SE preceding the onset of BED. A retrospective interview‐based design was used to compare 107 patients with BED and 107 patients with bulimia nervosa (BN), matched for duration of illness. Compared with patients with BN, those with BED reported a greater number of traumatic events in the 6 months preceding onset, revealing more often three types of events: bereavement, separation from a family member and accidents. The presence of SE before onset showed a dose–response relationship with the severity of psychopathology at the time of referral for treatment. Study of SE in patients with BED may be important for better understanding of the pathogenetic pathway to this disorder and to provide adequate treatment. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.